Environmental Research from Here and There: Numerical Modelling Labs as Heterotopias. (April 2015) - Laborde, Sarah
This paper examines the production of local and remote knowledge about the flows of a large Italian lake (Lake Como) on the basis of a dual ethnographic engagement with lake fishermen and computer modellers. The focus is the relationship between these two ways of knowing a lake, in relation to the lake itself and the places where the knowledge is produced. I first argue that despite being seemingly located at different edges of the environmental knowledge spectrum—the local and the remote and computer-mediated—the fishermen's and scientists' knowledges emerge from similar forms of skilled engagement in their respective environments. In other words, knowledge develops in place and fisherman and scientist do not know the same place in different ways; rather they know different places in similar ways. This raises the question of what kind of places these environmental modelling labs and offices are, and how they relate to the places they talk about, which are located elsewhere. I propose here the use of Michel Foucault's concept of heterotopia to model this complex articulation of the 'here' and 'there' in environmental modelling.